Assessment of Exposure to Aluminum through Consumption of Noodle Products - Nalinrat Kongta; Kunchit Judprasong; Rodjana Chunhabundit; Jintana Sirivarasai; Weeraya Karnpanit (Foods, 2023)
This study aimed to determine aluminum (Al) contents in commonly consumed noodles and estimate the risk of Al exposure through the consumption of noodles in the Thai population. A total of 80 samples, 20 samples each of rice stick noodles, egg noodles, wide rice noodles, and Thai rice noodles was purchased from markets in Bangkok Metropolitan and other four provinces in each region of Thailand. Wet digestion and graphite furnace atomic absorption spectrometry (GFAAS) were used to determine Al contents. Exposure assessment of Al was conducted by applying the consumption amounts of noodles from the national consumption survey and the Al contents of the noodle samples. The hazard quotient (HQ) was calculated to estimate the risk of exposure to Al. Aluminum contents in the noodles ranged from not detected to 630 mg/kg. Exposure to Al from consumption of each noodle product in all age groups was lower than the provisional tolerable weekly intake (PTWI). However, Al exposures in children calculated from the high consumer models and Al exposures in all age groups from the worst-case scenarios were higher than the PTWI, indicating potential adverse health effects. Consumers who regularly consume large amounts of noodle products containing Al may be at risk of having adverse health effects.